“Russian Muzhiks – Who Else if not Russians…”: Why Gogol is so Difficult to Translate: «Русские мужики? Какие же, как не русские…», или Почему трудно переводить Гоголя - Blizniuk-Biskup, Jekaterina (Przegląd Wschodnioeuropejski, 2019)
The author addresses the issue of how peculiarities of Gogol’s narrative style can be retained in the translations of “Petersburg Stories” and “Dead Souls”, with special focus on the attitude of the narrator towards what is reported. The main attention is paid to constructions with the qualificator russkij ‘Russian’ referring to phenomena deeply rooted in Russian culture and, on the face of it, serving to highlight the national “local color”. Still, on a closer inspection one finds that, contrary to expectations, relevant constructions reflect alienation of the narrator with respect to reported events, being a kind of exoticisms and thus additionally complicating translation. It is well-advised for Gogol’s translators to be mindful of this special variety of exoticization characteristic of his prose.